2022
DOI: 10.3389/fbioe.2021.828577
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Wall Shear Stress and Plaque Composition in Advanced Human Carotid Atherosclerosis

Abstract: The role of wall shear stress (WSS) in atherosclerotic plaque development is evident, but the relation between WSS and plaque composition in advanced atherosclerosis, potentially resulting in plaque destabilization, is a topic of discussion. Using our previously developed image registration pipeline, we investigated the relation between two WSS metrics, time-averaged WSS (TAWSS) and the oscillatory shear index (OSI), and the local histologically determined plaque composition in a set of advanced human carotid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Two different types of lesion formation were observed for the group with most significant flow disturbance and the one with the least severe flow disturbance. This finding is in agreement with a previous study, in which wall shear stress was shown to influence remodeling 44 , 45 . For group C (>90% ligation), more compliant vessels were observed.…”
Section: Discussionsupporting
confidence: 94%
“…Two different types of lesion formation were observed for the group with most significant flow disturbance and the one with the least severe flow disturbance. This finding is in agreement with a previous study, in which wall shear stress was shown to influence remodeling 44 , 45 . For group C (>90% ligation), more compliant vessels were observed.…”
Section: Discussionsupporting
confidence: 94%
“…Atherosclerosis is thought of as subject to a triad of, and especially interactions among, systemic risk factors, haemodynamic forces, and the biological response of the wall ( 2 ). Atherosclerosis is related to systemic risk factors, which can be aggravated by lifestyle factors such as high caloric diet, physical inactivity, and smoking, but atherosclerosis is, in a sense, a geometrically focal disease ( 3 , 4 ). Plaque progression and eventually plaque rupture is influenced by a complex interaction between biological and haemodynamic factors ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plaque progression and eventually plaque rupture is influenced by a complex interaction between biological and haemodynamic factors ( 5 ). The initiation of plaque formation has been strongly linked to a hemodynamic parameter: wall shear stress (WSS) ( 4 ). WSS is the frictional force exerted by flowing blood on the vessel wall, which significantly influences the evolution of atherosclerotic disease ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study combining CFD with pathology found necrotic core size and macrophage area are significantly larger in areas exposed to high TAWSS. The vulnerability exhibited by CEUS was also not statistically different between the two groups [37]. Moreover, basic studies have demonstrated that higher WSS plays a crucial role in the expression of vascular endothelial growth factor and endothelial NO synthesis [38, 39], which is believed to be a major mechanism for neovascularization and increased endothelial permeability [40, 41].…”
Section: Discussionmentioning
confidence: 99%